Aminomethylated Calix[4]resorcinarenes as Modifying Agents for Glycidyl Methacrylate (GMA) Rigid Copolymers Surface - Velásquez-Silva, Betty Astrid (Polymers (Basel), 2019)
Functionalization of tetrapropylcalix[4]resorcinarene, tetrapentylcalix[4]resorcinarene, tetranonylcalix[4]resorcinarene, and tetra-(4-hydroxyphenyl)calix[4]resorcinarene by means of aminomethylation reactions with the amino acids β-alanine and l-proline in the presence of aqueous formaldehyde was carried out. When β-alanine was used, the reaction products were tetrabenzoxazines. The reaction with tetra-(4-hydroxyphenyl)calix[4]resorcinarene did not proceed under the experimental conditions; therefore, l-proline was used, and the corresponding tetra-Mannich base was regio- and diasteroselectively formed. The products were characterized via FT-IR, (1)H NMR, (13)C NMR, and elemental analysis. With these aminomethylated-calix[4]resorcinarenes, the chemical surface modification of the copolymers poly(GMA–co–EDMA) and poly(BMA–co–EDMA–co–MMA) in a basic medium was studied. The results were quite satisfactory, obtaining the corresponding copolymers functionalized by nucleophilic substitution reaction and ring-opening between the carboxyl group of the upper rim of aliphatic calix[4]resorcinarenes and the hydroxyl group of the lower rim in the aromatic calix[4]resorcinarene and the epoxy group of the glycidyl methacrylate residue of each copolymer. The modified copolymers were characterized via FT-IR, scanning electron microscopy imaging, and elemental analysis. Finally, the modified copolymer surfaces exhibited interaction with peptides, showing their potential application in chromatographic separation techniques such as high-performance liquid chromatography.